Colorectal cancer and trace elements alteration - Juloski, Jovan T.; Rakic, Aleksandar; Ćuk, Vladica V.; Ćuk, Vladimir M.; Stefanović, Srđan; Nikolić, Dragica; Janković, Saša; Trbovich, Alexander M.; De Luka, Silvio R. (Journal of trace elements in medicine and biology, 2020)
•Significant alterations of Na, K, Mg, Ca, Cu, Zn, Se, Mn, Cd, Cr and Hg in malignant tissue of CRC compared to adjacent healthy bowel tissue were found.•Cu/Zn ratio was significantly higher in CRC tissue and in patients with higher CRC stages.•Male subjects with CRC had significantly higher Ca2+ tissue levels compared to female subjects with CRC. Trace elements have important influence on body function primarily because of the vital role they have in many physiological processes. Their alterations have been found in many disorders, including cancer. It has been well known for decades that disturbances in elemental concentration may lead to cell damaging, DNA injuries and imbalance in oxidative burden. Our study tried to determine the difference of trace elements concentrations between colorectal adenocarcinoma and adjacent healthy intestinal tissue. 59 subjects participated in this study. Healthy colon mucosa samples and colon tumor tissue samples were obtained from patients previously diagnosed with colon carcinoma by standard diagnostic procedures. Analysis of the elements was performed by inductively coupled plasma mass spectrometry (ICP-MS). The results showed that Na, K, Mg, Ca, Cu, Zn, Se, Mn, Cd, Cr and Hg significantly differ between malignant tissue of colorectal cancer (CRC) and adjacent healthy bowel tissue. We have, also, found that Cu/Zn tissue ratio was significantly higher in CRC compared to a healthy tissue and that patients with higher CRC stages had also significantly higher ratio. Since this is the first such study in Balkan region, we assume that results of our study could be a good indicator of elemental alterations in colorectal cancer of Balkan population, due to similarity in lifestyle, dietary intake, pollution and exposure to toxic elements.